Production cost of ice slurry using a saline solution and different ice mass fractions, applied to “Perico” (Coryphaena Hippurus) artisanal fishing in Peru - Milón Guzmán Juan José; Braga Sergio Leal; del Carpio Beltrán Herbert Jesús; Díaz Coa Mario Enrique (E3S Web of Conferences, 2021)
An experimental study was carried out to determine the production costs of ice slurry, using a saline solution with different fractions of ice, for “Perico” (Coryphaena Hippurus) artisanal fishing in the Peruvian sea. A 3-kW ice slurry generator, portable enough to fit in an artisanal boat, was used. The prototype was instrumented with sensors for temperature, density, and electrical parameters (voltage, current, power) measurement in order to determine the ice mass fraction and production costs. The results indicated that not only ice slurry ensures a higher cooling speed and less damage to the product, but also, its production costs are lower compared to flake ice.